2018
DOI: 10.1002/smj.2915
|View full text |Cite
|
Sign up to set email alerts
|

Time compression (dis)economies: An empirical analysis

Abstract: Research Summary: To investigate time compression diseconomies (TCD), this study estimated time–cost elasticities using 459 oil and gas global investment projects (1997–2010). Results show that the average cost of accelerating investments is negative: a firm could cut $6.3 million in costs of a single project by accumulating asset stocks 1 month faster. About 88% of the projects exhibit negative time–cost elasticities with over 39% of unrealized economies of time compression. Only 12% of the projects are subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Thus far, there has been surprisingly little empirical work on TCD, and existing studies have reached mixed conclusions. Hawk, Pacheco‐de‐Almeida, and Yeung (2013) have shown that the cost of building petrochemical plants increases as time is compressed, though firms may ultimately benefit from speeding up (Hawk & Pacheco‐de‐Almeida, 2018). Knott, Bryce, and Posen (2003) have demonstrated that TCD has a very limited effect on catch‐up ability in the pharmaceutical industry, whereas Vermeulen and Barkema (2002) and Jiang, Beamish, and Makino (2014) have illustrated that speed negatively influences success in international expansion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, there has been surprisingly little empirical work on TCD, and existing studies have reached mixed conclusions. Hawk, Pacheco‐de‐Almeida, and Yeung (2013) have shown that the cost of building petrochemical plants increases as time is compressed, though firms may ultimately benefit from speeding up (Hawk & Pacheco‐de‐Almeida, 2018). Knott, Bryce, and Posen (2003) have demonstrated that TCD has a very limited effect on catch‐up ability in the pharmaceutical industry, whereas Vermeulen and Barkema (2002) and Jiang, Beamish, and Makino (2014) have illustrated that speed negatively influences success in international expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Knott, Bryce, and Posen (2003) have demonstrated that TCD has a very limited effect on catch‐up ability in the pharmaceutical industry, whereas Vermeulen and Barkema (2002) and Jiang, Beamish, and Makino (2014) have illustrated that speed negatively influences success in international expansion. In a recent review of the work on TCD, Hawk and Pacheco‐de‐Almeida (2018) conclude, “In sum, TCD have been a longstanding theoretical principle with important implications for multiple strands of literature in management science; yet, we have only sparse and outdated empirical evidence of their existence” (p. 2491). Thus, further empirical work on TCD is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, slower firms also risk being preempted by faster competitors, resulting in potentially higher costs from late entry due to having a later pick on desirable sites, or later access to key suppliers or customers (Lieberman & Montgomery, 1988. A recent study found a substantial amount of time inefficiency across firms (Hawk & Pacheco-de-Almeida, 2018), suggesting that many firms face these potentially higher costs from being a slower firm.…”
Section: Speed In Investment Project Developmentmentioning
confidence: 99%
“…The M&A synergy issue touches on many key research streams in the strategy literature. For instance, it includes the ideas of the resource-based view of the firm and VRIO framework [6], the framework of recombinant innovation [7], the speed of strategic decisions [8], the real options perspective [9], and cultural factors in strategic management [10]. These research streams rely on heterogeneous sets of assumptions and have diverse theoretical origins.…”
Section: Competence-based Synergies In Mandamentioning
confidence: 99%